A COMPOSITE INDICATOR OF HOUSEHOLD DEMAND FOR DEBT (KONSTRUKCJA WSKAŹNIKA ZŁOŻONEGO POPYTU NA KREDYT GOSPODARSTW DOMOWYCH) - Białowolski, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
In this paper we present a novel approach for construction of a leading indicator for household demand for debt, i.e. consumer credit demand index. In order to derive the proper set of indicators we first present a theoretical background for the dimensions of the index. With all dimensions of the index at hand we search for indicators in the State of the Households Survey and consumer finance survey. We later aggregate the dimensions into a single index with generalized mean which does not allow for full compensability between dimensions. Finally, we check the leading properties of the index.